Conversational Hypnosis: Conceptual and Technical Differences Relative to Traditional Hypnosis. Issue 2 (4th September 2018) - Short, Dan
Abstract : This article provides an overview of conversational hypnosis (CH) as distinct from traditional forms. The article includes a history of Ericksonian hypnosis followed by a conceptual model and operational definitions for CH. The analysis is built on three levels of comparison and contrast. Three concepts commonly used in the general hypnosis literature—focusing, engaging, and inciting—structure a comprehensive definition of CH. The article concludes with recommendations for future research.